ANALISIS WACANA KRITIS MODEL VAN DIJK TERHADAP BERITA ONLINE “GADUH PEDULILINDUNGI DITUDING MELANGGAR HAK ASASI MANUSIA, ADA APA?” - Amellia Oktiaputri (Jurnal Semantik, 2023)
The purpose of this study is to describe the online news text entitled “Gaduh PeduliLindungi Dituding Melanggar Hak Asasi Manusia, Ada Apa?” on the official website nasional.tempo.co using the Teun A. Van Dijk Critical Discourse Analysis approach. The method used is a qualitative method with a Critical Discourse Analysis approach using the Teun A. van Dijk model. The data analysis technique used in this research is content analysis technique. The results of this study show that in the text dimension found text elements, coherence (including additive coherence, conditional coherence, differentiating coherence), negation, sentence form, pronouns, setting, details, intent, lexicon, and graphics. This dimension shows that the US government’s accusations were refuted by parties related to the PeduliLindungi application maker which clearly did not violate human rights and was made in accordance with application governance. In social cognition, it was found that journalists showing partiality to the government regarding reporting on the PeduliLindungi application through published news, while the social context shows that social during the pandemic has led to new habits, in the form of changes in people’s social behavior in various aspects of life.